তাজউদ্দীন আহমদের সমাজ ও রাষ্ট্রভাবনা : নির্বাচিত বক্তৃতা - আহমদ, তাজউদ্দীন, ১৯২৫-১৯৭৫. (ঢাকা : প্রতিভাস, 2011)
Selected speeches of Tājauddina Āhamada, 1925-1975, politician and first Prime Minister of Bangladesh, on contemporary socio-political issues of Bangladesh.
Donated By Akbar Ali Khan
In Bengali.
Keywords: Bangladesh -- Politics and government -- 1971-; Bangladesh -- Social conditions -- 20th century